Studies on the prevalence of zoonotic important protozoan parasite Sarcocystis sp. in Nepal - Rana, Hari Bahadur; Manandhar, Krirshna Das (Journal of Advanced Academic Research, 2017)
Sarcocystosis is a disease caused by Sarcocystis sp. of protozoan parasite and it has a zoonotic aspect. Four hundred forty one water buffaloes (Bubalus bubalis) were examined to assess zoonotic important protozoan and helminth parasites. Among them 441 buffalo samples were observed, only 285 (64.63%) buffaloes were infected with protozoan and helminth parasites. The total prevalence rate of protozoan parasite Sarcocystis sp. was the highest 124 (43.51%). The prevalence rate of five different areas of the country, the highest prevalence rate was found in Butwal 37 (49.46%) followed by Dharan 26 (48.14%), Kathmandu 22 (46.80%), Chitwan 38 (41.30%) and Nepalganj 18 (32.72%). So, in Nepal Sarcocystis sp. was most common parasite of water buffaloes and most of the human infection occurs by ingestion of raw or improperly cocked meat of infected animals. The risk of infection of Sarcocystis sp. was very high but not yet paid attention neither from the Government nor from the private sectors.Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 147-149